TERAPI STIMULASI KOGNITIF UNTUK LANSIA DENGAN MILD COGNITIVE IMPAIRMENT STUDI EKSPERIMENTAL DI PANTI WREDA - Nathalie Sanchia,* Magdalena Surjaningsih Halim* (NEURONA, 2019)
INTRODUCTION MILD COGNITIVE IMPAIRMENT MCI IS A TRANSITIONAL STAGE BETWEEN THE ELDERLYS NORMAL EXPECTED COGNITIVE DECLINE AND THE MORE SERIOUS DECLINE CAUSED BY DEMENTIA THAT NEEDS INTERVENTIONS ONE OF THE NONPHARMACOLOGICAL INTERVENTIONS THAT CAN BE DONE IS COGNITIVE STIMULATION THERAPY CST RESEARCH HAS SHOWN THAT CST CAN STABILIZE AND IMPROVE COGNITIVE FUNCTION IN THE ELDERLY WITH MCI